CONCEPTIONS OF STUDENTS AT RISK ON BEHAVIOR MODIFICATION PROGRAM CREATE: A STORY OF ONE PUBLIC SCHOOL IN THE PHILIPPINES - Barela, Rosalie Nenette S.; Bernardino, Hedivina P.; Ana, Veronida M.; Feliciano, Analyn C.; Averion, Rebecca F. (PEOPLE: International Journal of Social Sciences, 2018)
Students’ misbehavior in the classroom is a common scenario. In some researches, students’ misbehavior is associated with social skill deficiency resulting in behavior problems and poor academic achievement. This study is timely and vital in addressing the need for a program that will reinforce positive discipline in the classroom. The Edukasyon sa Pagpapakatao (EsP) of Benjamin B. Esguerra Memorial National High School (BBEMNHS) maintains that the intervention program with the goal to Change, Reinvent, and Elevate Attitude Towards Excellence (CREATE) of students that are at risk is essential to lessen if not eradicate misbehavior in the classroom. Both quantitative and qualitative approaches were utilized, particularly pre-test and post-test quasi-experimental design and phenomenographical analysis. Survey questionnaire, anecdotal records, and focus group interviews were used for data gathering. This research was anchored on the inculcation approach of set absolute values processed according to social skills processing of change: seeing, thinking, and doing. The common classroom misbehaviors such as not submitting projects/homework, cutting classes, absenteeism, and violating school rules were garnered from the respondents. Interactive games are found to be the most effective among the enabling activities. Lectures are perceived to be the least effective. Pre-test and post-test of the respondents’ social skills have significant difference, while, students’ conceptions on the effect of the CREATE program generate a binary opposite effect such as acceptance vs. denial, resolve vs. status quo, and applying vs. defying. Further studies in gender and grade level implementation of the program may be undertaken using this baseline research.